FINANCIAL PRODUCTION IN ISLAM - Bayinat Basha Al-Bajali, Abul Firdaus (IJRDO - Journal of Business Management, 2016)
Worship includes every human movement in life, and accordingly a person’s quest for gain is worship, and he is rewarded for it as long as he adheres to what he is obligated to do in it. The research has been called just earning; Because the meaning of justice is a comprehensive meaning to address many things, it is more general from the word of the halal or crusher, and human must be amounting to himself and with others, Allaah says: you remember.In my research, (production financing in Islam) I dealt with some of the production issues from a Quranic perspective by explaining its importance, responsibility, objectives, controls and financing, explaining the difference between the concept of production and the concept of earning, then the production controls and production financing in Islam, then the conclusion of the chapter was with a statement of the alternatives in investment and financing by participation. in the capital. For this reason, I extrapolated the verses in which the conditions of earning are mentioned in the Noble Qur’an, using the inductive method, then I interpreted the verses and explained hadiths, criticism and deduction. Using the analytical method, then I showed the teachings to which the verses guide us, which must be applied in dealing with people through the applied approach.